Spiritual Entrepreneurship: An Approach to Understanding Christian Spirituality in Market Place - Ignatius Bambang Sukarno Hatta; Romi Lie (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
Efforts to explore the spirituality of Christian work have become an urgent need, not because they want to compete with the spirituality of work that is currently going on in a secular manner, but as a form of fulfilling the Christian missionary call to "witness, preach the Gospel, and make disciples of all nations." Apart from being an effort to fulfill the call of Christian mission, studying the spirituality of Christian work also helps Christian workers to have a quality work ethic in their workplace, because they do it productively, independently and spiritually. Spiritual entrepreneurship was found to be the right choice that could meet the criteria and forms of Christian work spirituality needed. The method used in this research is literature study, namely by collecting data from books, the Bible, and online journals about Christian entrepreneurship, Christian work spirituality, and Christian work ethic. Spiritual entrepreneurship is the best choice as an embodiment of the spirituality of Christian work, because of the consideration of the underlying principles and values, its distinctive form, and its function and the possibility of a large positive impact it can generate.